Coronary Collateral Growth Induced by Physical Exercise: Results of the Impact of Intensive Exercise Training on Coronary Collateral Circulation in Patients With Stable Coronary Artery Disease (EXCITE) Trial. Issue 15 (12th April 2016) - Möbius-Winkler, Sven; Uhlemann, Madlen; Adams, Volker; Sandri, Marcus; Erbs, Sandra; Lenk, Karsten; Mangner, Norman; Mueller, Ulrike; Adam, Jennifer; Grunze, Martin; Brunner, Susanne; Hilberg, Thomas; et al.
Abstract : Background—: A well-developed coronary collateral circulation provides a potential source of blood supply in coronary artery disease. However, the prognostic importance and functional relevance of coronary collaterals is controversial with the association between exercise training and collateral growth still unclear. Methods and Results—: This prospective, open-label study randomly assigned 60 patients with significant coronary artery disease (fractional flow reserve ⩽0.75) to high-intensity exercise (group A, 20 patients) or moderate-intensity exercise (group B, 20 patients) for 4 weeks or to a control group (group C, 20 patients). The primary end point was the change of the coronary collateral flow index (CFI) after 4 weeks. Analysis was based on the intention to treat. After 4 weeks, baseline CFI increased significantly by 39.4% in group A (from 0.142±0.07 at beginning to 0.198±0.09 at 4 weeks) in comparison with 41.3% in group B (from 0.143±0.06 to 0.202±0.09), whereas CFI in the control group remained unchanged (0.7%, from 0.149±0.09 to 0.150±0.08). High-intensity exercise did not lead to a greater CFI than moderate-intensity training. After 4 weeks, exercise capacity, VO2 peak and ischemic threshold increased significantly in group A and group B in comparison with group C with no difference between group A and group B. Conclusions—: A significant improvement in CFI was demonstrated in response to moderate- and high-intensity exercise performed for 10 hours per week. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01209637.